A new record of a small cyprinid, Oreichthys cosuatis (Hamilton, 1822) in the Ganga River, India: New record of O. cosuatis in Ganga - Alam, Absar; Verma, Sushil Kumar; Kumar, Jeetendra; Nath Jha, Dharm; Rama Rao Thakur, Venkatesh; Shukla Das, Shyamal Chandra; Mishra, Sandeep Kumar; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2023)
Oreichthys cosuatis (Hamilton, 1822) is a small indigenous fish of the tropics with very little scientific information. It belongs to the family Cyprinidae. O. cosuatis was reported to occur in countries like Bangladesh, Pakistan, Thailand, Myanmar, and India. The natural distribution of O. cosuatis is not well documented and its distribution in Indian waters is questionable due to its misidentification. The germplasm exploration studies in the River Ganga from July 2016 to October 2019 confirmed the first record of Oreichthys cosuatis (Hamilton, 1822) along with some morphological descriptions from fifteen individuals in the middle stretches of the River Ganga at Bijnor, Uttar Pradesh, India.